AN ANALYSIS OF SPEECH ACTS IN THE MOVIE “MONTE CARLO” BY THOMAS BEZUCHA - Khaeratun Niswati; Mahyuni; Arafiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Speech acts are essential for effective communication, as they involve not just the content of a message but also how it is conveyed and understood by the listener. They play a crucial role in maintaining relationships between speakers and listeners. As a core aspect of pragmatics, speech acts help us interpret the meaning behind utterances, including apologies, requests, complaints, and other forms of communication.This study focuses on analyzing illocutionary, locutionary, and perlocutionary acts in the Monte Carlo movie using qualitative research. This approach relies on the researcher's expertise in analyzing data rather than on numerical or statistical information. In the movie, 69 locutionary acts are identified, where characters express ideas without necessarily expecting the listener to be convinced or take action. The film also features 173 illocutionary acts, with directives—commands or requests—being the most common. These acts are followed by 58 representative acts, in which characters assert beliefs to persuade the listener. Perlocutionary acts, which are the effects these speech acts have on the listener, often result from directive illocutionary acts. Sometimes, these lead to non-verbal responses, such as the listener rejecting the speaker's direction. The study highlights the significance of understanding these speech acts in communication.